Does Rubella Cause Autism: A 2015 Reappraisal? - Hutton, Jill (Frontiers in Human Neuroscience, 2016)
In the 1970s, Stella Chess found a high prevalence of autism in children with congenital rubella syndrome (CRS), 200 times that of the general population at the time. Many researchers quote this fact to add proof to the current theory that maternal infection with immune system activation in pregnancy leads to autism in the offspring. This rubella and autism association is presented with the notion that rubella has been eliminated in today’s world. CRS cases are no longer typically seen; yet, autistic children often share findings of CRS including deafness, congenital heart defects, and to a lesser extent visual changes. Autistic children commonly have hyperactivity and spasticity, as do CRS children. Both autistic and CRS individuals may develop type 1 diabetes as young adults. Neuropathology of CRS infants may reveal cerebral vasculitis with narrowed lumens and cerebral necrosis. Neuroradiological findings of children with CRS show calcifications, periventricular leukomalacia, and dilated perivascular spaces. Neuroradiology of autism has also demonstrated hyperintensities, leukomalacia, and prominent perivascular spaces. PET studies of autistic individuals exhibit decreased perfusion to areas of the brain similarly affected by rubella. In both autism and CRS, certain changes in the brain have implicated the immune system. Several children with autism lack antibodies to rubella, as do children with CRS. These numerous similarities increase the probability of an association between rubella virus and autism. Rubella and autism cross many ethnicities in many countries. Contrary to current belief, rubella has not been eradicated and globally affects up to 5% of pregnant women. Susceptibility continues as vaccines are not given worldwide and are not fully protective. Rubella might still cause autism, even in vaccinated populations.